(untitled) (Agro Productividad, 2020)
Objective: to assess the production of basil (Ocimum basilicum L.) grown in a greenhouse under open hydroponic system, using tezontle (volcanic gravel) as substrate. Methodology: three planting densities were evaluated: D1, D2 and D3 (14, 28 and 71 plants m-2, respectively) and two concentrations of Steiner nutrient solution (S1: 100%, and S2: 50%). Results: the highest values for fresh and dry weight of the aerial part, were the treatments S1 D1, S1 D2 and S2 D1. With S1 D1 the largest leaf area was obtained. Dry matter obtained was 14.03 mg g-1 of essential oil. Findings: the use of hydroponics with an increase in sowing density can generate up to 70.21 t ha-1.